The Effects of Hydration Parameters and Co-Surfactants on Methylene Blue-Loaded Niosomes Prepared by the Thin Film Hydration Method - Li Key Yeo; Cheng Shu Chaw; Amal Ali Elkordy (MDPI AG, 2019)
This work aimed to investigate and optimise the effects of co-surfactants, hydration volume, and time on the entrapment of methylene blue (MB) within niosomes and the vesicle sizes of MB-loaded niosomes upon different storage temperatures. Niosomes were prepared by the thin film hydration method followed by gel permeation chromatography to obtain purified niosome suspensions. The probe sonication method was used to reduce the niosome vesicle size and distribution. Highest entrapment efficiencies (%EE) were determined for niosomal formulations containing Span® 60, cholesterol, and Cremophor® ELP (E2 and E3), which were prepared with a hydration volume of 5 mL. The hydration time was 15 min for E2 and 60 min for E3 (%EE = 40.1 ± 7.9% and 32.9 ± 10.1% for E3 and E2, respectively). The final lipid contents in the formulations were shown to have an impact on %EE.